Thermo-mechanical behavior of organic-inorganic halide perovskites for solar cells. (June 2018) - Ramirez, Cristina; Yadavalli, Srinivas K.; Garces, Hector F.; Zhou, Yuanyuan; Padture, Nitin P.
Abstract: Organic-inorganic halide perovskites (OIHPs) are a remarkable family of hybrid materials at the heart of the emerging thin-film perovskite solar cells (PSCs) technology and other applications. In this Viewpoint article, in addition to some original experimental results, thermo-mechanical analyses of residual macro- and micro-stresses in OIHP thin films are presented in the context of fracture of both the OIHP layer itself and its interface with the substrate. The implications of mechanical behavior of OIHPs and interfaces on the reliability of PSCs, as well as opportunities for future research directions in this general area, are highlighted. Graphical abstract: Unlabelled Image